2017
DOI: 10.5114/aic.2017.66185
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a single episode of remote ischemic preconditioning on myocardial injury after elective percutaneous coronary intervention

Abstract: IntroductionMyocardial injury after percutaneous coronary intervention (PCI) occurs in approximately 30% of procedures, and is related to worse prognosis. Effects of remote ischemic preconditioning (RIPC) on reperfusion injury have been investigated before, yielding conflicting results.AimTo assess the impact of a single episode of RIPC on myocardial injury after elective PCI.Material and methodsOne hundred and four patients undergoing elective PCI, with normal baseline cardiac troponin-I (cTn-I) values, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
2
2
Order By: Relevance
“…They implied that shorter time of RIPC could be an insufficient stimulant, resulting neutral outcome. Differently, Zografos et al, demonstrated reduced type 4a MI after elective PCI with one cycle of RIPC, whereas in our study we could not demonstrate a significant reduction (7,8) . Six year clinical outcomes of the patients enrolled in CRISP trial were also published and the results were coherent with the CRISP trial with lower MACE in the RIPC group (5,9) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…They implied that shorter time of RIPC could be an insufficient stimulant, resulting neutral outcome. Differently, Zografos et al, demonstrated reduced type 4a MI after elective PCI with one cycle of RIPC, whereas in our study we could not demonstrate a significant reduction (7,8) . Six year clinical outcomes of the patients enrolled in CRISP trial were also published and the results were coherent with the CRISP trial with lower MACE in the RIPC group (5,9) .…”
Section: Discussioncontrasting
confidence: 99%
“…However, the best timing and protocol has not been determined yet. In one study, it has been demonstrated that one cycle of RIPC is also effective in reducing post-PCI myocardial injury, whereas in our study with a similar study population, we could not demonstrate cardioprotection with one cycle of RIPC (7)(8) . Most of the studies about RIPC evaluated myocardial injury by post-PCI cardiac enzyme elevation, there are a few studies with clinical endpoints.…”
Section: Introductioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Eleven trials reported cardiac troponin levels 16 hours 2123 or 24 hours 2431 after elective PCI. RIC was not associated with a reduction of cardiac biomarker release ( n =2048, SMD 0.06, 95% CI −0.17 to 0.30; P =0.59, I 2 =85%) with very high heterogeneity (Supplementary Appendix 6).…”
Section: Resultsmentioning
confidence: 99%